Attitude Calculation Algorithm for Quadrotor UAV Based on Acceleration Correction Model - Fan, Hongbo (International Journal of Computer Science and Information Technology, 2024)
To enhance the accuracy of quadrotor UAV navigation systems in dynamic environments, we propose an attitude calculation method based on an acceleration correction model. This model estimates and corrects non-gravitational acceleration from the accelerometer, reducing its impact on attitude calculation. Experimental results demonstrate that this algorithm effectively mitigates non-gravitational acceleration interference and significantly improves the accuracy and anti-interference capability of UAV navigation systems.